PEMBAHARUAN DALAM PEMBAHARUAN - Saidul Amin (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Egypt and India are the two centers of world civilization that gave birth to philosophical thought and tamaddun. These two areas have ecperienced ups and downs and ups and downs, both when standing alone or when colonized by foreign nations. Such conditions would have different impacts, both positive and negative. Negative aspects of giving birthor in children’s mental colony complex lander. While the positive aspects of growing patriotic souls among his people. It is natural that these two regions spemd a lot of great characters, among them Muhammad ‘Abduh and Ahmad Khan. Both these figures are considered a corner stone for the renewal of Islam in their respective continents. There are similarities but also many differences in principle between the two thoughts. Event intellectuals often assume both the Muslims and the west are at a parallel. Is it true? So this study tries to analyze the two men thought of the aspects of similarities and differences to answer all the doubts and confusion that ever existed.